Linguistic Occurrences in the Poetic Works of Lasgush Pogradeci PeculiaritÃ del linguaggio poetico di Lasgush Poradeci - Seitllari, Liri (Mediterranean Journal of Social Sciences, 2012)
Article aims to discover the Lasgush Pogradeci's approach to the Albanian language ; to enlighten his opinion about thelanguage and its particular role in poetry.Therefor , we will stop at poetry "Fiery Languageâ€ and then we will examine in a moreexpanded and more specific way the linguistic occurrences in his poetic books : â€˜The dance of the starsâ€ and â€œThe star of the heartâ€™ , byclaiming to bring new insights and somehow enrich studies of linguists to date on his work. Linguistic occurrences such as phonologicalstreams through his verses, use of the old mastery of the original traits of words, special arrangements and links of words , the poetry ofcommon vocabulary, high semantic intensity of words generated by him , the special place of exclamatory and their emotionalâ€“expressive values . At the end , we can say that Lasgush Pogradeci is an elite poet , because he has the skills to work in elite way withthe language ; achieving a high level of aesthetic language